Formal Thought Disorder and Self-Disorder: An Empirical Study - Nordgaard, Julie; Gravesen-Jensen, Mette; Buch-Pedersen, Marlene; Parnas, Josef (Frontiers in Psychiatry, 2021)
Background Formal thought disorder was constitutively linked to the original concept of schizophrenia and has since been one of central features supporting its diagnosis. Bleuler considered formal thought disorder as a fundamental symptom of schizophrenia among other fundamental symptoms, including ego-disorders. The contemporary concept of self-disorder represents a more developed, nuanced, and systematic approach to disturbances of self-experience than the Bleulerian concept of ego-disorders. Since fundamental symptoms, on Bleuler’s account, are persistently present in every case, an association between these symptoms could be expected. The purpose of this study was to examine the association between self-disorder and formal thought disorder. Methods A sample of 94 diagnostically heterogeneous patients were examined for formal thought disorder using clinical rating and a proverb test. The proverb test was analyzed for 2 different aspects of formal thought disorder: literal responses and bizarre responses. The sample was comprehensively assessed for psychopathology, including self-disorder as measured with the EASE scale. Results The patients, who provided bizarre responses, had a higher level of self-disorder, more negative symptoms, lower level of social functioning, and lower level of intelligence. Bizarre answers aggregated in patients diagnosed within the schizophrenia spectrum compared with patients outside the schizophrenia spectrum. We found moderate correlations between the 2 measures of formal thought disorder (clinically rated and bizarre responses) and self-disorder (0.454 p<0.01, and 0.328 p<0.01). Literal responses did not differ between diagnostic groups and did also not correlate with bizarre responses. Specificity of bizarre responses for a diagnosis within schizophrenia-spectrum was 86.89%, whereas sensitivity was 40.85%. Conclusion The close relation between formal thought disorder and self-disorder further adds to the notion of self-disorder as a unifying psychopathological core beneath the apparently heterogenous symptoms of schizophrenia.